Widening contexts for processability theory theories and issues - Lenzing, Anke; Nicholas, Howard; Roos, Jana (Processability approaches to language acquisition research & teaching ;, 2019)
"This book explores relationships between Processability Theory approaches and other approaches to SLA. It is distinctive in two ways. It offers PT-insiders a way to see connections between their familiar traditions and theories with other ways of working. Parallel to this it offers readers who work in other traditions ways of connecting with a research tradition that makes precise testable claims about second language acquisition processes. These dual perspectives mean that both beginning and established SLA researchers as well as those seeking to connect their work with views of language learning will find something of interest. Studies of multiple languages and multiple aspects of language are included. Chapters cover areas as diverse as literacy, language comprehension, language attrition and language testing"--